FAZLUR RAHMAN’S THOUGHTS ON EDUCATION AND THEIR RELEVANCE TO THE CONTEMPORARY ISLAMIC EDUCATION WORLD - Alsadika Ziaul Haq; Maragustam; Usman (CV. TOTUS TUUS, 2026)
The contemporary Islamic education system is facing significant challenges due to the rapid pace of globalization, technological advancements, and ideological changes. These challenges call for an adaptive educational model that balances traditional Islamic values with modern educational needs. Fazlur Rahman (1919–1988), a prominent Muslim philosopher, provided essential insights into this issue. Rahman critiqued the intellectual stagnation within the Muslim world and the division between religious and secular knowledge. His educational philosophy promotes a holistic integration of science, ethics, and methodology, advocating for a system that nurtures not just intellectual capabilities, but also moral and spiritual development. This study aims to analyze Rahman’s thoughts on Islamic education and explore their relevance in addressing the current issues within contemporary Islamic education. Using a qualitative approach and library research, this paper examines Rahman’s works, particularly his hermeneutical method of double movement, and their implications for modern Islamic curricula. The study finds that Rahman’s approach can provide a progressive framework for Islamic education, emphasizing critical thinking, moral integrity, and the integration of religious and general knowledge. Rahman’s educational philosophy is crucial in reshaping Islamic education to meet contemporary demands without losing its Islamic identity.